The Influence of Live Streaming, Content Marketing, and Brand Ambassadors on Purchasing Decisions for Fashion Products on TikTok - Safina, Maria; Kusuma, Kumara Adji; Sari, Dewi Komala (LifeSciFi, 2025)
This study aims to determine the effect of live streaming, content marketing, and brand ambassadors on purchasing decisions for fashion products of Pilotter on the TikTok shopping platform. A quantitative approach was used, with a population consisting of the people of Pasuruan and Sidoarjo. The sample consisted of 100 respondents, selected using a purposive sampling technique based on the criteria of individuals from the Pasuruan and Sidoarjo communities who have purchased the product on the TikTok shopping platform. Data were collected through the distribution of questionnaires. Data analysis was conducted using IBM SPSS Statistics Version 26 for Windows, employing multiple linear regression analysis, validity testing, reliability testing, normality testing, multicollinearity testing, heteroscedasticity testing, t-test, F-test, and coefficient of determination analysis. The results of the study show that live streaming, content marketing, and brand ambassadors influence purchasing decisions. Live streaming and brand ambassadors have a significant effect on purchasing decisions, whereas content marketing does not have a significant effect. The findings imply that businesses should prioritize live streaming strategies and the use of brand ambassadors to enhance purchasing decisions on the TikTok shopping platform.